Impact of Spleen Size on Outcomes in Laparoscopic Splenectomy in Children. (28th September 2015) - Karadag, Cetin Ali; Erginel, Basak; Kuzdan, Ozgur; Sever, Nihat; Akın, Melih; Yıldız, Abdullah; Dokucu, Ali İhsan
Abstract : Background . The aim of our study is to compare the efficacy of laparoscopic splenectomy (LS) between enlarged spleens and normal sized spleens. Methods . From June 2006 to September 2012, 50 patients underwent LS. The patients consisted of 24 girls and 26 boys with the mean age of 8.64 years (1–18). The patients are divided into two groups according to spleen's longitudinal length on the ultrasonography. Group I consisted of the normal sized spleens; Group II consisted of spleens that are exceeding the upper limit. Groups are compared in terms of number of ports, operative time, rate of conversion to open procedure, and length of hospital stay. Results . The mean number of ports was 3.27 and 3.46, the mean length of the operation was 116.36 min and 132.17 min, rate of conversion to open procedure was 9.09% and 10.25%, and the mean length of hospital stay was 3.36 days and 3.23 days, respectively, in Group I and Group II. Although there is an increase in the number of the ports, the operative time, rate of conversion to open procedure, and the length of hospital stay, the difference was not significant between groups (P > 0.05 ). Conclusion . LS is safe and effective in enlarged spleens as well as normal sized spleens.